Pengendalian Serangan Rayap Tanah Coptotermes sp. Menggunakan Ekstrak Daun Belimbing Wuluh (Averrhoa bilimbi L) - Zulkahfi Zulkahfi; Suterayani Suparmin; Sutami Suparmin; Astuti Arif (Hasanuddin University, 2017)
Bilimbi or cucumber tree often be used from almost all parts of the plant as a traditional medicine. In addition, people often use the leaves as a material for insects, especially to make flies away from food. The information of local knowledge that bilimbi leaves contains insect control. The purpose of this study was to control of subterranean termites attack using extract of bilimbi (Averrhoa bilimbi L) leaves. The powder of the plant leaves was extracted using ethanol solution. The extracts were then prepared in different concentrations, namely 2%, 4%, and 6%. Paper discs with 25 mm diameter were immersed in the each of the concentration. The other treated paper discs used chlorpyrifos as positive treatment. Untreated paper discs were also prepared as control. In this study, only one of tests were applied, which were contact poison. The effectiveness of the extract was determined based on the termite mortality and weight loss of the paper discs. Results showed that treatment has a very significant effect on the value of mortality. Treatment of various concentrations of bilimbi leaf extract significantly different from the control and termiticide. Treatment of bilimbi leaf extract concentration and termitisida show 100% mortality whereas control only amounted to 23.64%. Keywords: Averrhoa bilimbi L, control, termite, extract, effectiveness